2019
DOI: 10.1093/qjmam/hbz019
|View full text |Cite
|
Sign up to set email alerts
|

Time to Approach Similarity

Abstract: Summary In a recent article, Ball and Huppert (J. Fluid Mech., 874, 2019) introduced a novel method for ascertaining the characteristic timescale over which the similarity solution to a given time-dependent nonlinear differential equation converges to the actual solution, obtained by numerical integration, starting from given initial conditions. In this article, we apply this method to a range of different partial differential equations describing propagating gravity currents of fixed volume as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…With these two intuitive observations in mind, we can guess that p decreases with τ and diverges as p → 0 + . The exact analytic dependence is not straightforward, but Ball & Huppert (2019) and Webber & Huppert (2019) showed that the inversely proportional relationship (τ ∝ p −1 ) works as an excellent first-order approximation for the radially symmetric case. Although the exact proportionality for the power-law channel might differ from the radially symmetric case, we can assume that…”
Section: Outflow From the Originmentioning
confidence: 99%
See 2 more Smart Citations
“…With these two intuitive observations in mind, we can guess that p decreases with τ and diverges as p → 0 + . The exact analytic dependence is not straightforward, but Ball & Huppert (2019) and Webber & Huppert (2019) showed that the inversely proportional relationship (τ ∝ p −1 ) works as an excellent first-order approximation for the radially symmetric case. Although the exact proportionality for the power-law channel might differ from the radially symmetric case, we can assume that…”
Section: Outflow From the Originmentioning
confidence: 99%
“…The method of similarity calculates the behaviour of the current using scaling symmetry, and the solution derived represents the current in a stationary condition when the memory of the initial conditions are lost, which within a finite time scale, differs from the real flow depending on how it is released. Ball & Huppert (2019) and Webber & Huppert (2019) discuss the time scale at which an axisymmetric current converges to the self-similar solution. A similar construction is used herein to investigate the time scale of real flow approaching the similarity solutions, and we found different leading-power terms from the axisymmetric case studied by Ball & Huppert (2019) and Webber & Huppert (2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time taken to approach this one-eighth power law is evidently very short in this experiment. This 'adjustment time' has been recently investigated by Ball & Huppert (2019) and Webber & Huppert (2020) for the case of gravitational spread of a viscous fluid (Huppert 1982). They found that this time, somewhat independent of initial conditions, can be just fractions of a second in laboratory experiments, but many days in geological situations, where the extremely viscous lava domes from volcanic eruptions can eventually spread horizontally to hundreds of kilometres.…”
Section: The Squeezing Problem (F > 0)mentioning
confidence: 99%
“…an analytical function [5]. Note that such a solution is not expected to hold close to the initial state, being therefore valid on a relatively long timescale [27,28]. This theoretical solution can be used as long as capillary effects can be disregarded, i.e., the height of the current is larger than the capillary length.…”
Section: Introductionmentioning
confidence: 99%